Future socioeconomic changes - Notenbaert, An Maria Omer; Vervoort, Joost M.; Snel, D. (HEALTHY FUTURES project, 2013)
Development of socio-economic scenarios and translating them into suitable storylines and provide an overview of potential data to be used for a quantification of future disease vulnerabilities